Pengaruh Media Simpan Serbuk Gergaji Dan Sekam Terhadap Viabilitas Benih Kakao (Theobroma Cacao L.) - Gunawan, Bambang; Pratiwi, Yeni Ika; Hariyadi, Bambang W.; Thoyib, M. (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
Cocoa is a plant with recalcitrant seed properties. The viability of recalcitrant seeds canonly be maintained for a few weeks or months, even though they are stored in optimumconditions. Cocoa seeds need to be maintained viability during storage / shipping to thedestination of planting. The purpose of this study was to determine the effect of sawdust andhusk storage media on the viability of cocoa seeds (Theobroma cacao L.). The results showedthat: a). Storage treatments using sawdust and husk storage media have a significant effect onthe percentage (amount) of germination seeds, speed or rate of sprouts and wet weight of cocoaseed sprouts; b). The treatment of K4 (storage with 100% husk) tends to give a better valuecompared to other treatments on all variables studied, so that cocoa seeds can be maintainedviability during storage / shipping to the destination of planting.Keywords: Viability Of Cocoa Seeds, Recalcitrant, Seed Technology, Sawdust, Huks